PERANCANGAN DAN ANALISIS CARBODY LOKOMOTIF DENGAN METODE ELEMEN HINGGA - Arief Herman Soesilo; Fadelan Fadelan; Wawan Trisnadi Putra (KOMPUTEK, 2020)
A locomotive is one of critical part in train set, because a locomotive had to bear a big load and has operational time which long enough. So in a locomotive design required more in depth analysis compared to the other means of transportation. The purpose of this research is to make a design locomotive carbody according to those standards applied and analyze stress happened to carbody locomotive designed. In the design of this to analyze carbody locomotive construction strength, the analysis are done using finite element methode(FEM) with help of Ansys software. The simulation of loads working on the structure was made approaching the real loading. Structure of locomotive carbody should be able to hold the loads working on carbody construction. From the design results locomotive carbody that have been made, this locomotive carbody sized length 19000 mm, width 2790 mm, and high 3700 mm. Materials that used for the locomotive carbody design isSS 400 and SM 490A with Yield stress of 245 MPa dan 325 MPa. The analysis results received a value of von mises stress maximum of 195,429 MPa that occurs at the part of the end of underframe (end center sill), where the sress value are still below of Yield stress materials which are in the form of SM 490 at 325 MPa. From the analysis result suggests that overall locomotive carbody structure can be expressed as safe and able to hold the loads operational.